2023
DOI: 10.1101/2023.03.22.533820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing vaccine-mediated protection in an ultra-low doseMycobacterium tuberculosismurine model

Abstract: Despite widespread immunization with Bacille-Calmette-Guerin (BCG), the only currently licensed tuberculosis (TB) vaccine, TB remains a leading cause of mortality globally. There are many TB vaccine candidates in the developmental pipeline, but the lack of a robust animal model to assess vaccine efficacy has hindered our ability to prioritize candidates for human clinical trials. Here we use a murine ultra-low dose (ULD) Mycobacterium tuberculosis (Mtb) challenge model to assess protection conferred by BCG vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These data corroborate other recent work showing that BCG reduces detectable infection and disseminated infection in addition to traditional bacterial load measurements, although these studies required substantially larger numbers of mice due to the lower protective efficacy of BCG. 19 , 20 Therefore, the capacity of ΔLprG to abrogate detectable infection and disseminated infection with relatively small group sizes may provide an experimentally tractable model for assessing potent vaccines such as ΔLprG, including facilitating mechanistic studies evaluating immune molecules and subsets in mediating defined aspects of protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data corroborate other recent work showing that BCG reduces detectable infection and disseminated infection in addition to traditional bacterial load measurements, although these studies required substantially larger numbers of mice due to the lower protective efficacy of BCG. 19 , 20 Therefore, the capacity of ΔLprG to abrogate detectable infection and disseminated infection with relatively small group sizes may provide an experimentally tractable model for assessing potent vaccines such as ΔLprG, including facilitating mechanistic studies evaluating immune molecules and subsets in mediating defined aspects of protection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, BCG provides long-term bacterial control in the low-dose model, in contrast to the short-lived protection observed after 100 CFU challenge. 20 Use of challenge strain barcoding 18 , 20 and analysis of spleen and other sites of dissemination like draining lymph nodes could provide a more granular understanding of vaccine protection. In addition, future studies could assess the contributions of myeloid and T cell subsets as well as the cytokines identified in our correlates analysis for their potential roles as regulators of ΔLprG vaccine protection in the low-dose model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this ULD model, a blood RNA signature was identified that could predict the severity of TB disease in NHP. Recently, the ULD mouse model was used to evaluate the protective efficacy of BCG vaccination, with the important finding that BCG could prevent infection in some of mice 119 . Therefore, the ULD model could represent an important advance in the use of mice to model TB vaccine responses.…”
Section: Using Genetically Diverse Mouse Modelsmentioning
confidence: 99%
“…The major caveat of the C57BL/6 model lies in the lack of human-like pathology. Of note, application of ultra-low dose infection (ULD) ( 56 ) may render these mice amenable for pathology studies ( 57 ). Upon ULD, mice develop single, structured lesions upon inhalation of 1-3 Mtb CFU of the laboratory strain H37Rv.…”
Section: Small Animal Modelsmentioning
confidence: 99%